Conceptual framework of built environment factors on cycling behavior among residential neighborhoods / Norhazlan Haron ... [et al.] - Haron, Norhazlan; Zainol, Halmi; Wan Omar, Wan Rabiah; Sallehu, Noor Syarafina; Mohamad bahari, Noor Ashikin (2020)
Cycling is one of transport mode that support physical activity as well as promote healthy environment in residential areas. Although cycling is beneficial, it has been found that cycling activities in the neighborhood were not one of the main physical activities. Previous research has shown that this was due to characteristics of built environment were not encouraging enough for existing and potential cyclists. The purpose for this study is to identify built environment determinant that influence the level of cycling activity of residential neighborhood. Those determinants were extracted from content analysis of previous studies related to cycling and built environment entity. The main aspect to determine the relationship between all built environment factors that influence behavior of individuals and personal characteristics. The result of analysis showed that all physical and built environment factors are potentially become catalyst to cycling activity among residential neighborhood. The study also found that bicycle infrastructure related with cycling behavior and environment. This research was considered in promoting residential proper planning of residential neighborhood by enhancing actual and perceived environmental conditions. The new conceptual framework of cycling behavior is expected to help designers, planners in producing a better and active lifestyle within neighborhoods.